Control de calidad fisicoquimico de formas farmacéuticas en el laboratorio Hypatia S. A., enero – diciembre” 2015” - Avila Parrera, Anderson Gianfranco (2016)
This report of professional practices aimed to describe the activities you performed in the area of quality control of pharmaceutical products developed in the HYPATIA S. A. Laboratory, which is dedicated to providing training and quality control testing of pharmaceutical products , health products and medical devices, also verification tests, calibration and qualification of equipment and instruments, in accordance with national and international official techniques and when it is applicable according to origin laboratory techniques are also made, besides at the request of its users it develops and / or validates analytical techniques and conducts research in the area of competence. The results in this report show activities in the area of quality control, using pharmacopoeial methods (USP, BP and EP) and origin laboratory techniques; and to determine the dosage form has a higher frequency identification chemical assay, dissolution, content and content uniformity